Inhibitory Effect of Lactococcus lactis subsp. lactis HFY14 on Diphenoxylate-Induced Constipation in Mice by Regulating the VIP-cAMP-PKA-AQP3 Signaling Pathway - Tan Q; Hu J; Zhou Y; Wan Y; Zhang C; Liu X; Long X; Tan F; Zhao X (Dove Medical Press, 2021)
Qian Tan,1,2,* Jing Hu,3,* Yujing Zhou,1,2 Yunxiao Wan,1,2 Chuanlan Zhang,1,2 Xin Liu,1,2 Xingyao Long,1,4 Fang Tan,5 Xin Zhao1 1Chongqing Collaborative Innovation Center for Functional Food, Chongqing Engineering Research Center of Functional Food, Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, 400067, People’s Republic of China; 2College of Biological and Chemical Engineering, Chongqing University of Education, Chongqing, 400067, People’s Republic of China; 3Department of Pharmacy, Southwest Hospital, Army Medical University (Third Military Medical University), Chongqing, 400038, People’s Republic of China; 4Department of Food Science and Biotechnology, Cha University, Seongnam, 13488, South Korea; 5Department of Public Health, Our Lady of Fatima University, 838 Valenzuela, Philippines*These authors contributed equally to this workCorrespondence: Xin ZhaoChongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Xuefu Main Street 9, Chongqing, 400067, People’s Republic of ChinaTel +86-23-6265-3650Email zhaoxin@cque.edu.cnFang TanDepartment of Public Health, Our Lady of Fatima University, 120 McArthur Highway, 838 Valenzuela, PhilippinesTel +86-23-6265-3650Email tanfang@foods.ac.cnAim: The naturally fermented yak yogurt of pastoralists in the Tibetan Plateau, China, because of its unique geographical environment and the unique lifestyle of Tibetan pastoralists, is very different from other kinds of sour milk, and the microorganisms it contains are special. Lactococcus lactis subsp. lactis HFY14 (LLSL-HFY14) is a new lactic acid bacterium isolated from naturally fermented yak yogurt. The purpose of this study was to study the inhibitory effect of the bacterium on constipation.Methods: Constipation was induced in ICR mice with diphenoxylate, and the constipated mice were treated with LLSL-HFY14. The weight and feces of the mice were visually detected. Colonic tissues were observed on hematoxylin and eosin-stained sections. Serum indices were detected with kits. mRNA expression in the colon was determined by quantitative polymerase chain reaction assay.Results: Constipation caused weight loss, the number of defecation granules, defecation weight, fecal water content decreased, and the first black stool excretion time increased. LLSL-HFY14 alleviated these symptoms, and the effects were similar to those of lactulose (drug). The pathological examination revealed that constipation caused pathological changes in the colon, and LLSL-HFY14 effectively alleviated the disease. LLSL-HFY14 increased serum levels of motilin, gastrin, endothelin, substance P, acetylcholinesterase, and vasoactive intestinal peptide (VIP) and decreased serum levels of somatostatin in constipated mice. In addition, LLSL-HFY14 upregulated VIP, cAMP, protein kinase A, and aquaporin 3 expression in colonic tissues of constipated mice in a dose-dependent manner.Conclusion: LLSL-HFY14 inhibited constipation, similar to lactulose, and has the potential to become a biological agent.Keywords: yak yogurt, lactic acid bacterium, diphenoxylate, constipation, mice